What Moves Capital to Transition Economies? - Mora, Nada (IMF Working Papers; Working Paper ;, 2002)
Between 1991 and 1999, capital flows to 25 transition economies in Europe and the former Soviet Union differed widely in terms of overall levels and the share and composition of private flows. With some exceptions (notably Russia), the main form of private inflows was foreign direct investment. Portfolio investment was volatile and concentrated in a handful of countries. Regressions show that direct investment can be well explained in terms of economic fundamentals, whereas the presence of a financial market infrastructure and a property-rights indicator are the only explanatory variables that seem to have had a robust effect on portfolio investment.